Hand abnormalities in diabetics: Prevalence and predictors in Erbil city - Al-Barzinji, Niaz J.; Mohammed, Wallada Khalid (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: The characteristics of diabetic foot disease are well documented in Erbil city; henceforth it would be appropriate to evaluate the problem of diabetic hand syndrome in this environment and to assess the frequency and the most important clinical and biochemical risk factors for the development of these complications. Methods: This is an observational case-control study done over a period of one year. A total of 100 consecutive patients with type 2 diabetes mellitus were enrolled and described as cases. One hundred age- and sex-matched nondiabetic individuals were taken in the control group; all were examined and then underwent the appropriate investigations. Results: Of the total 100 diabetic patients, 63% had macrovascular complications and 60% had one or more hand disorders. Limited joint mobility (47% vs. 18%, respectively; P = 0.0001) and Dupuytren’s contracture (16% vs. 2%, respectively; P = 0.001) were significantly higher in type 2 diabetes mellitus patients than in the controls, but not trigger finger. These hand soft-tissue changes correlated significantly with poor glycemic control. Conclusion: This study shows a high prevalence of hand disorders in diabetic patients with the limited joint mobility being the most common hand disorder. The hand soft tissue changes are under recognized in diabetic patients, occurring in 60% of the cases. We recommend that physicians should consider examining the periarticular region of the joints in the hands in each diabetic patient.